Intracellular Condensates of Oligopeptide for Targeting Lysosome and Addressing Multiple Drug Resistance of Cancer. Issue 1 (10th October 2021) - Wang, Jing; Hu, Liangbo; Zhang, Hongyue; Fang, Yu; Wang, Tingliang; Wang, Huaimin
Abstract: Biomolecular condensates have been demonstrated as a ubiquitous phenomenon in biological systems and play a crucial role in controlling cellular functions. However, the spatiotemporal construction of artificial biomolecular condensates with functions remains challenging and has been less explored. Herein, a general approach is reported to construct biomolecular condensates (e.g., hydrogel) in the lysosome of living cells for cancer therapy and address multiple drug resistance induced by lysosome sequestration. Aromatic‐motif‐appended pH‐responsive hexapeptide (LTP) derived from natural insulin can be uptaken by cancer cells mainly through caveolae‐dependent endocytosis, ensuring the proton‐triggered phase transformation (solution to hydrogel) of LTP inside the lysosome specifically. Lysosomal hydrogelation further leads to enlargement of the lysosome in cancer cells and increases the permeability of the lysosome, resulting in cancer cell death. Importantly, lysosomal assemblies can significantly improve the efficiency of current chemotherapy drugs toward multidrug resistance (MDR) cells in vitro and in xenograft tumor models. As an example of functional artificial condensates in lysosomes, this work provides a new strategy for controlling functional condensates formation precisely in the organelles of living cells and addressing MDR in cancer therapy. Abstract : Lysosome selective construction of biomolecular hydrogel with emerging biological functions provides a novel strategy for controlling cancer cell fates by inducing lysosomal‐membrane permeabilization and addressing multidrug resistance in a tumor‐bearing mouse model.